Integrating Bilingual Literacy with Batik Workshop for Empowering Indonesian Labourers’ Children - Mochamad Nuruz Zaman; Shohenuddin; Reza Sukma Nugraha; Edy Ismail; Mulyono; Muhammad Nurtanto; Nur Kholifah (International Journal of Community Service Learning, 2025)
Field surveys reveal a concerning literacy gap among the children of Indonesian migrant workers, with a substantial proportion demonstrating English proficiency levels significantly below the national average for their age group in Malaysia. This disparity not only hinders their academic achievement but also constrains future opportunities, underscoring the urgent need for targeted interventions. This community service program aimed to address the educational and cultural challenges faced by Indonesian migrant worker children abroad. The project employed a descriptive qualitative approach involving 20 Indonesian migrant children in Malaysia as participants. Data were collected through observation and structured interviews and analyzed using thematic analysis techniques. The findings indicate that batik-making training combined with bilingual literacy education strengthened the children’s connection to their national identity while improving their literacy skills in both Indonesian and English. The program also promoted sustainability by incorporating environmentally friendly batik practices. In conclusion, the initiative proved effective in fostering cultural pride, academic development, and transferable skills among participants. The program offers important implications for cross-cultural educational development models designed to support migrant worker children overseas.